Weird Earth : Debunking Strange Ideas about Our Planet - Prothero, Donald R. (Book collections on Project MUSE., 2020)
Applying his extensive scientific knowledge, Prothero corrects misinformation that con artists and quacks use to hoodwink others about geology--hollow earth, expanding earth, and bizarre earthquakes--and mystical and paranormal happenings--healing crystals, alien landings, and the gates of hell. By deconstructing wild claims such as prophesies of imminent natural disasters, Prothero provides a way for everyone to recognize dubious assertions. Prothero answers these claims with facts, offering historical and scientific context in a light-hearted manner that is accessible to everyone, no matter their background. With a careful layering of evidence in geology, archaeology, and biblical and historical records, Prothero's Weird Earth examines each conspiracy and myth and leaves no question unanswered.